Correlation of Sex Hormones and Periodontal Disease in Women with Menstrual Cycle Irregularities - Noora Abd Awad; Noor Hazim Abdulkareem; Elham Hazeim Abdulkareem; Shaimaa Sabte Mutlak (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background & Objectives: Variations in the levels of female sex hormones,i.e., estrogen and progesterone,are responsible for various physiological changes,including those in the oral tissues. The aim of this researchis to determine the effects of changes in sex hormone levels in women with irregular periodsand sufferingfrom periodontal diseases in comparison to healthy women.Methods: This study included70 subjects who visited the Clinic at the Department of Periodontology,College of Dentistry,University of Anbar, during the period of July 2019to September 2019. The gingivalcrevicular fluid(GCF) was collected from the patient group (35 females with irregular periodsand periodontaldisease) and the control group(25 healthy females).Results: Compared to control, asignificantlyhighermean concentration of GCFestradiolwas found in thepatient group. Additionally, the patient group also exhibited a significantly lower mean concentration ofGCFprogesterone compared to the control group.Interpretation & Conclusion: Changes in sex hormonesaresignificantlycorrelated with periodontal tissuechangesand GCF examination can be used as a non-invasive method to detect these hormonal changes.Thisstudy demonstrated that GCF could prove to be a good, non-invasive method to validate the levels of sexhormones in females with periodontal diseases.